1995
DOI: 10.1086/133660
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Atlas of the Arcturus Spectrum, 0.9-5.3 microns

Abstract: ABSTRACT. A spectral atlas of the infrared spectrum of the bright K2 giant Arcturus has been completed using the 4-m Mayall telescope and FTS. The 0.9-5.3 ¡im spectrum of Arcturus was observed at high signal to noise with a resolution of 100,000. Telluric lines were removed by using telluric transmission spectra generated from McMath-Pierce solar spectra or 4-m lunar spectra. The spectrum of Arcturus was observed on two different dates selected to give large opposite heliocentric shifts. The spectra observed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
357
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(367 citation statements)
references
References 7 publications
6
357
1
Order By: Relevance
“…The EWs for these lines have been measured only when they appear to be Doppler shifted away from the telluric components, as judged by referring to the Arcturus spectrum (Hinkle et al 2000).…”
Section: Line Selectionmentioning
confidence: 99%
“…The EWs for these lines have been measured only when they appear to be Doppler shifted away from the telluric components, as judged by referring to the Arcturus spectrum (Hinkle et al 2000).…”
Section: Line Selectionmentioning
confidence: 99%
“…Each order of the spectrum has been flattened and the continuum set to 1, but there remain slight variations, and the use of an interactive measure allows the continuum level to be set locally. Line blanketing is significant in these cool and metal-rich stars, so we used the high-resolution spectrum of Arcturus (Hinkle et al 2000), convolved to our observed resolution, to aid in determining the continuum level. Because our analysis was ultimately done relative to Arcturus, all lines were also measured from the original, high-resolution Arcturus spectrum.…”
Section: Equivalent Widthsmentioning
confidence: 99%
“…We used the identifications given in the infrared atlas of Arcturus (Hinkle et al 1995), the line lists provided by Kurucz & Bell (1995), the list of iron lines in Nave et al (1994), the HITRAN database from Rothman et al (2008), and the identifications of SiO and OH lines at 4 μm given in Ridgway et al (1984). The attribution of atomic or molecular transitions to the observed features was based on identifications for similar stars presented in the literature or the most probable origin of the line, and have in some cases been verified by spectral modelling.…”
Section: Line Identificationsmentioning
confidence: 99%
“…As a result, line data for many elements, but especially the post-iron group elements, are severely lacking and those that exist are predominantly the result of theoretical calculations. The atlases of the solar spectrum (Wallace et al 1996;Delbouille et al 1973) and the K giant Arcturus (Hinkle et al 1995) illustrated the value of a stellar reference spectrum at high spectral resolution and high S/N.…”
Section: Introductionmentioning
confidence: 98%